Efeito de isolados de Bacillus spp,E Trichoderma spp. No crescimento de Fusarium oxysporum f. sp. lycopersici agente causal da fusariose do tomateiro. - Lima, Odenilson de Deus Ribeiro (2012)
Among the most economically important diseases affecting tomato stands out Fusariosis, caused by the fungus Fusarium oxysporum f. sp. lycopersici. The deficiency in controlling this disease, associated with environmental conditions favorable to the fungus, unfeasible economic tomato cultivation in the state of Maranhão. In this context, alternative production systems may be important in reducing the environmental and social impacts. The objective of this study was to evaluate the quality of antagonism and metabolites produced by different species of Bacillus in vitro mycelial control and biocontrol effect of Trichoderma spp. against F. oxysporum f. sp. lycopersici. For evaluation of antagonistic Bacillus on F. oxysporum f. sp. lycopersici was performed pairing of fungus and bacteria in vitro method by Circle. The experimental design was a completely randomized design with 11 treatments and five replications. In the method for detection of products secreted by Bacillus metabolites were prepared 200 ml portions of BD (Potato Dextrose) in Erlenmeyer flasks, and those discs transferred to PDA medium containing the bacterium (Bacillus spp.) Remaining in camera 15 days BOD. After this period there was added 3 g of agar per vial, being autoclaved broth and poured into Petri dishes. In the center of the plates were placed in culture dishes pathogen being evaluated at the tenth day. The experimental design was completely randomized with six replications and 11 treatments. For evaluation of antagonistic Trichoderma spp. on F. oxysporum f. sp. lycopersici was performed pairing of cultures. The experimental design was a completely randomized design with 11 treatments and five replications. In the production of volatile metabolites of Trichoderma spp. Was used the technique of overlapping plates. We used ten isolates of Trichoderma spp., and each treatment consisted of a single most control, with five repetitions. In the production of non-volatile metabolites, we used the membrane filter technique. In the experiment, the treatments were arranged in a completely randomized design with five replicates. Differences between means were determined by the Tukey test at 5 %. In the experiment evaluating the antagonism to F. oxysporum f. sp. lycopersici with the use of Bacillus, all isolates were statistically different from control with emphasis on isolated B12 (Bacillus sp.), B41 (Bacillus cereus), B22 '(Bacillus pentothenticus), B45 (Bacillus cereus), B47 (Bacillus cereus ) and B25 (Bacillus pumilus) that induced the lowest average colony diameter of the pathogen. To study the inhibition of mycelial growth of F. oxysporum f. sp. lycopersici by agar sterilized by ten isolates of Bacillus spp., five isolates differed significantly from the control they are: B35 (B. pumilus), B47 (Bacillus cereus), B22 '(B. pentothenticus), B12 (Bacillus sp.) and B41 (B. cereus) the latter two treatments that showed the best results of the pathogen colony diameters with 2.89 and 3.81 cm, respectively. All isolates differ from the control on the antagonistic action of Trichoderma, showing efficient in inhibiting the mycelial growth of F. oxysporum f. sp. lycopersici, but there was no significant difference among the isolates. Through the technique of overlapping plates, the isolates that showed the best results were T7 and T8, which inhibited 24.5 % of mycelial growth of the pathogen, standing out from the others, yet this inhibition was not less than 50 %, and then, the isolates classified as inefficient. Regarding the assessment of the effect of metabolites not voltáteis, isolates that showed the best results were T3, T10, T11, T12, T13, and T14, differing from the others, stand out isolates T12 and T14 for presenting percentage greater than 50% inhibition, and these isolates also classified as moderately effective